Pediatric Chondroblastoma and the Need for Lung Staging at Presentation. Issue 9 (October 2020) - Arkader, Alexandre; Williams, Amy; Binitie, Odion; Thacker, Mihir M.; Farfalli, German L.
Abstract : Purpose: Chondroblastoma is a benign, but potentially locally aggressive, bone tumor with predilection for the epiphysis of long bones in growing children. Historically, there is a reported 2% risk of lung metastasis, however these cases are mostly in the form of isolated single reports and the vast majority in adults. The purpose of this study was to identify the "true" risk of lung metastases at presentation in skeletally immature patients with a benign chondroblastoma, and therefore revisit the need for routine chest staging. Methods: This was a multi-institution, international retrospective study of children and adolescents diagnosed and treated for a benign chondroblastoma. We focused on the screening and diagnosis of lung metastasis, type of staging utilized and the incidence of local recurrence. Detailed review of the available literature was also performed for comparison. Results: The final studied cohort included 130 children with an average age of 14.5 years (range: 6 to 18 y). There were 94 boys and 36 girls. Lesions more often involved the proximal humerus (32/130), proximal tibia (30/130), and proximal femur (28/130). At an average follow-up of 50 months, there were 15 local recurrences (11% rate) and no cases of lung metastasis. All patients underwent chest imaging at presentation. The overall reported lung metastases rate in the pulled literature review (larger series only) was 0.4% (7/1625), all patients were skeletally mature. Conclusions: This is the largest cohort of pediatric-exclusive chondroblastoma in the literature. Despite minor differences in management between the centers included, the recurrence rate was similar and there was no evidence of lung metastasis (0 in 130). The incidence of distant involvement in a true benign chondroblastoma in children is much lower than the 2% previously reported in the literature, and the need for routine chest staging should be revisited. Level of Evidence: Level III.